Infrastructure and the Energy Use of Human Polities. (April 2023) - Freeman, Jacob; Baggio, Jacopo A.; Miranda, Lux; Anderies, John M.
This paper integrates scaling theory with variation in systems of governance to help explain cross-cultural differences in the energy use of human polities. In both industrial and pre-industrial polities, systems of governance moderate the scaling of population and energy use. Polities with more inclusive governance systems display, on average, lower energy use per agent. However, as populations increase in size, the energy consumed by polities with more inclusive governance increases faster than among polities with less inclusive governance. These results support the hypothesis that more inclusive governance systems help generate a virtuous cycle of increasing trust, larger-scale cooperation, and more productive economies; however, a byproduct of this process is an expanding network–energy throughput tradeoff: Good governance empowers individuals and firms to connect and cooperate. At the same time, similar to Jevons' classic efficiency paradox, scaling-up this empowerment requires a system, as a whole, to consume ever greater amounts of energy and materials from the earth's ecosystems.